Digital Transformation in MSME Financial Management: Qualitative Evidence from Banten, Indonesia - Sukriyah Sukriyah; Bambang Suhartono; Firdaus Putra; Nelson Silitonga; Gusli Chidir (AGUSPATI RESEARCH INSTITUTA, 2026)
Digital transformation has become a critical pathway for strengthening financial management practices among micro, small, and medium enterprises (MSMEs), particularly in developing economies. Despite increasing access to digital financial technologies, empirical evidence indicates that many MSMEs adopt these tools in a fragmented and non-strategic manner. This study aims to explore how MSME actors experience digital transformation in financial management, identify the practical changes arising from the use of digital financial tools, and examine the barriers and enabling factors shaping this transformation. Employing a qualitative research design, this study draws on in-depth interviews, non-participant observations, and document analysis involving 24 MSME owners and managers across micro, small, and medium enterprises in Banten Province, Indonesia. Thematic analysis reveals that digital transformation among MSMEs unfolds incrementally, beginning with basic tools such as digital payments and mobile banking, largely driven by customer demand rather than strategic intent. While digital tools improve transaction recording accuracy, financial transparency, and operational efficiency, their utilization remains predominantly operational, with limited progression toward analytical or strategic financial management. Key challenges include inadequate digital and financial literacy, trust concerns related to data security, cost constraints, infrastructural limitations, and entrenched traditional practices. The findings underscore that digital transformation in MSME financial management is a socio-technical process shaped by interactions between technology, managerial capabilities, and institutional context. This study contributes to the literature by providing rich qualitative insights from an underexplored regional context and offers practical and policy-relevant implications for fostering inclusive, context-sensitive digital transformation among MSMEs.